(3JMdjd hJUeje GdefXeGJs - (3Ydj YHO GdgGOj(B, (3eSdes ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2002)
(3ebOeI aj GdefXeGJ hJWhQ GdacQ GdJfXjej, GdHjFI GdNGQLjI, GdJcfhdhLj, GdYeQ hGdMLe hOhQI MjGI GdefXeGJ, GdCgOGa hGdaGYdjI GdJfXjejI, UfY GdbQGQGJ GdGOGQjI, GdfahP hGdefGhQGJ(B.s
(3GdeQGLY U(B.233s
Keywords: (3GdEOGQI GdYGeIs; (3GdJfXje hGdEOGQIs; (3GdefXeGJ hGdgjFGJ(B- (3EOGQIs